Wykonaj mnożenie.
e) 2x²y×(x-y)×(x+y)=?
g) 4×(2xy²+3yz)×(2xy²-3yz)=?
h) 2×(3pq²-4)×(3pq²+4)=?
j) (3x-1)×(3x+1)×(2-x)=?
k) (3xy-y+3x)×(x-xy+y)=?
l) [2x-(b+a)]×[(a+b)+2x]=?
ł) (x²+4)×(x-2)×(x+2)=?
m) (2x-y)×(2x+y)×(4x²+y²)=?
Dam naj.odp.

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T22:35:49+01:00
G)4(2xy²+3yz)(2xy²-3yz)=4(4x²y⁴-6xy³z+6xy³z-9y²z²)=16x²y⁴-24xy³z+24zy³z-36y²z²=16x²y⁴-36y²z²

h)2(3pq²-4)(3pq²+4)=2(9p²q⁴+12pq²-12pq²-16)=18p²q⁴+24pq²-24pq²-32=18p²q⁴-32

j)(3x-1)(3x+1)(2-x)=(9x²+3x-3x-1)(2-x)=(9x²-1)(2-x)=18x²-9x²-2+x=9x²-2+x

k)(3xy-y+3x)(x-xy+y)=3x²y-3x²y²+3xy²-xy+xy²-y²+3x²-3x²y+3xy=-3x²y²+4xy²+2xy-y²+3x²

l)[2x-(b+a)][(a+b)+2x]=[2x-b-a][a+b+2x=2xa+2xb+4x²-ab-b²-2xb-a²-ab-2xa=4x²-2ab-b²-a²

ł)(x²+4)(x-2)(x+2)=(x²+4)(x²+2x-2x-4)=(x²+4)(x²-4)=x⁴-4x²+4x²-16=x⁴-16

m)(2x-y)(2x+y)(4x²+y²)=(4x²+2xy-2xy-y²)(4x²+y²)=(4x²-y²)(4x²+y²)=16x⁴+4x²y²-4x²y²-y⁴=16x⁴-y⁴
1 5 1